The growth opportunities for SMC? - Bentzen, Jan; Madsen, Erik Strøjer; Smith, Valdemar (Journal of Business Economics and Management, 2006)
The extensive empirical literature on the validity of Gibrat's law does not in general verify the law as it finds that firms’ growth rates are negatively correlated with both firm size and age. However, some studies find that Gibrat's law holds for sub‐samples of firms such as large firms or firms belonging to special industries. It has been pointed out that these results are due to the fact that the likelihood of firm survival for natural reasons is positively related to firm size and age. This study uses a relatively large and representative sample of Danish firms to evaluate the validity of Gibrat's law for different kinds of firms over the period 1990–2003. In contrast to the majority of earlier studies our analysis corrects for the bias in the estimations by using variables related to the survival of small firms.Firstd Published Online: 14 Oct 2010